2019
DOI: 10.1186/s12872-019-1113-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intermittent fasting on myocardial infarction-induced cardiac remodeling

Abstract: Background Information on the role of intermittent fasting (IF) on pathologic cardiac remodeling is scarce. We compared the effects of IF before and after myocardial infarction (MI) on rat cardiac remodeling and survival. Methods Wistar rats were intermittently fasted (food available every other day) or fed ad libitum for 12 weeks and then divided into three groups: AL – fed ad libitum; AL/IF - fed AL before MI and IF after MI; and IF – fed IF before and after MI. Echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…However, it was not possible to verify association between intermittent fasting and changes in MAPK protein expression. In a previous study, 39 intermittent fasting attenuated cardiac hypertrophy and ventricular dilation in infarcted rats, although it did not alter the gene expression of fetal peptides.…”
Section: Discussionmentioning
confidence: 66%
“…However, it was not possible to verify association between intermittent fasting and changes in MAPK protein expression. In a previous study, 39 intermittent fasting attenuated cardiac hypertrophy and ventricular dilation in infarcted rats, although it did not alter the gene expression of fetal peptides.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study examined the effect of alternate day fasting on cardiac remodeling post-myocardial infarction (MI) in rats. While IF improved cardiac function and reduced left ventricular dilation, none of the fibrosis gene markers examined appeared to have been affected (Okoshi et al, 2019). Another study showed that alternate day fasting promoted cardiomyocyte survival post-MI in rats by increasing the expression of antiapoptotic and angiogenic factors (Katare et al, 2009).…”
Section: Cardiometabolic Syndrome and Therapeutic Or Intermittent Fastingmentioning
confidence: 97%
“…A high-fat diet during gestation in several species causes deleterious effects in newborns; in particular, altered gene expression, abnormalities in the functions of antioxidant enzymes, the increased possibility of developing atherogenesis, and damage to the cardiovascular system [ 139 ]. The reduction of fatty acids intake generally has several benefits, such as a reduction in body weight, and cholesterol and triglyceride levels, and an improvement in the functioning of the myocardium [ 140 , 141 ]. Polyphenols are bioactive chemical compounds synthesized by plants that are mainly found in fruits and vegetables, where they are responsible for color, flavor, and many pharmacological activities.…”
Section: Diabetic Cardiomyopathy and Bergamot Polyphenolsmentioning
confidence: 99%